Hydroxychloroquine as antiviral prophylaxis for exposed caregivers to Covid-19: An urgent appraisal is needed - Rachid Tahiri Joutei Hassani; Ahmed Bennis (Elsevier, 2020)
Background: Since the onset of the new coronavirus pandemic, the world is facing a public health emergency. Repositioning hydroxychloroquine (HQ) seems to be a promising option. Many emerging evidences have converged on the effectiveness of HQ in the treatment of Covid-19 infection. In a recent paper, Gautret et al. suggested that further works are needed to determine if HQ antiviral prophylaxis is useful, especially for healthcare workers. Methods: The purpose of this paper is to assess the Covid-19 exposure and risks level among caregivers. For this, we performed research on internet and PubMed by crossing the following keywords: healthcare givers, healthcare workers, doctors, nurses, coronavirus, Covid-19, mortality, infection rate, chloroquine, hydroxychloroquine. Results: Data on healthcare worker's infection and mortality by Covid-19 are partial and are not systematically published. However, it seems that the infection rate varies between 3.8% and 9% depending on the country. Moreover, the mean age of this population is relatively old, especially in the OECD area. Conclusions: Anti-Covid-19 HQ prophylaxis should be urgently accessed, especially for healthcare workers. It is to be hoped that HQ prophylaxis reduces the morbidity and mortality from Covid-19 infection among this population which is particularly exposed and relatively old.